Juvenile corrections in the era of reform: a meta-synthesis of qualitative studies - Sankofa, Jub (International journal of offender therapy and comparative criminology, 2018)
In this article, the authors synthesize knowledge from select qualitative studies examining rehabilitation-oriented juvenile residential corrections and aftercare programs. Using meta-synthesis methodology, the authors extracted and coded content from 10 research studies conducted by five authors across criminology, sociology, and social welfare disciplines. The total number of published works based on those studies analyzed was 18. Collectively, these studies offer insight into three major components of the juvenile correctional experience: therapeutic treatment and evidence-based practices, the shaping of identities and masculinities, and preparation for reentry. This analysis is particularly important as the United States is currently in an era of reform during which policymakers are increasingly espousing the benefits of rehabilitation for youth offenders over punishment. These studies took place before, during, and after this era of reform, and yet, the findings are surprisingly consistent over time, raising key questions about the effectiveness of the reform strategies.